Preliminary in Vitro Investigations on The Inhibitory Activity of The Original Dietary Supplement Oxidal® on Pathogenic Bacterial Strains (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
The antimicrobial action of the dietary supplement Oxidal® was tested using the classic Bauer and Kirby agar-gel diffusion method. Clinical and reference strains of Staphylococcus aureus and Escherichia coli were used in the studies. The tested dietary supplement showed a well-pronounced inhibitory effect against the microbial strains commensurable with that of the broad-spectrum chemotherapeutic agent Enrofloxacin and showed even higher activity than the broad spectrum antibiotic Thiamphenicol. The proven inhibitory effect of the tested dietary supplement against the examined pathogenic bacteria is in accordance with the established clinical effectiveness standards for antimicrobial agents.